2013
DOI: 10.1111/meca.12016
|View full text |Cite
|
Sign up to set email alerts
|

The (Normal) Rate of Capacity Utilization at the Firm Level

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 44 publications
3
72
0
Order By: Relevance
“…Lavoie (, ) and Dutt () introduce the notion of expected rate of growth and argue that, in such a way, it is possible to ensure a stable long‐period equilibrium solution. Nikiforos (, ) criticizes these positions and proposes his own explanation of the endogeneity of the normal degree of utilization, which is based on the assumption of returns to scale that increase at a diminishing rate…”
Section: The Standard Model Of Growth With Unused Capacitymentioning
confidence: 99%
“…Lavoie (, ) and Dutt () introduce the notion of expected rate of growth and argue that, in such a way, it is possible to ensure a stable long‐period equilibrium solution. Nikiforos (, ) criticizes these positions and proposes his own explanation of the endogeneity of the normal degree of utilization, which is based on the assumption of returns to scale that increase at a diminishing rate…”
Section: The Standard Model Of Growth With Unused Capacitymentioning
confidence: 99%
“…Some recent contributions, however, have proposed new (non‐conventionalist) foundations for the convergence of the normal utilization rate to its current, actual value (Dávila‐Fernández, Oreiro, & Punzo, ; Nikiforos, ). This approach relies on a microeconomic model in which firms minimize costs under (a particular type of) increasing returns to scale (Nikiforos, ). Specifically, the model would imply a positive effect of the firm's output level on the firm's desired utilization rate.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, recent developments on production theory have showed that cost minimizing firms increase the utilization rate of their capital if the rate of returns to scale decreases as production increases, that is, the normal rate of utilization is endogenous to variations in demand (Nikiforos ). In the light of such recent contributions, this note also suggests that endogeneizing normal capacity utilization is a more appealing alternative.…”
Section: Introductionmentioning
confidence: 99%